The Impact of Family Control on Dividend Policy: Evidence from Indonesia - Atmaja, Lukas Setia (Universitas Prasetiya Mulya, 2016)
This paper examines the relationship between family control and dividend policy in Indonesia. There are three possible explanations for the relationship. The expropriation hypothesis predicts that family control has a negative impact on dividend payouts. Meanwhile the reputation hypothesis and the family income hypothesis predict that family control has a positive impact on dividend payouts. Using a panel data of Indonesian publicly listed firms in the period of 2003-2009, the results shows that family control has a significant negative impact on dividend payouts, dividend yields and likelyhood to pay dividends. The results control for other variables that may potentially affect dividend payments such as growth opportunity, debt, profitability, firm size and firm age. From agency theory perspective, the finding is consistent with the argument that family controlling shareholders prefer lower dividends, in order to preserve cash flows that they can potentially expropriate (the expropriation hypothesis).